DARE Newsletter, Vol. 12, No. 4, Fall 2009 - Rubrecht, August W.; Baker, Paul; DARE; Sorenson, Jon E. (Dictionary of American Regional English, 2009)
Contents: "A Few More That Got Away" by August Rubrecht; "Coming in Volume V"; " 'Arthur the Rat' Online"; "Video Lecture on DARE Available Online"; "Funding Update" by Jon E. Sorenson; "Looking It Up" by Paul Baker; "In Memoriam: William Safire"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Fieldwork; Americanisms; Dictionaries; Lexicography; Regional English; English Language--Dialects--United States